Small Medium Enterprises with Corporate Social Responsibility to be Part Supply Chain Management of Industry - Heru, Santoso; Egi, Abinowi (CENTRAL ASIA AND THE CAUCASUS, 2022)
SME or Small Medium Enterprises in general have financial and market problems. SME cannot market products because they do not have a market. There is no market so the product is not sold. Products that are not sold SME do not have income so that they have financial problems to keep the business running. One solution to the SME problem is CSR or Corporate Social Responsibility assistance. In this case the author tries to make a series of systems to be a solution.